2019
DOI: 10.1007/s42773-019-00020-7
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer and soil conditioner value of broiler manure biochars

Abstract: Pyrolysis is an option for enhancing the sustainable management of broiler manure surpluses by producing a concentrated, hygienic char product with a fertilizer and soil conditioner value. In this study, the impacts of pyrolysis conducted at 350, 400 and 450 °C on total nutrient and harmful element concentrations in biochars derived from peat-bedded broiler manure were examined. Emphasis was placed on the availability of phosphorus (P). In addition, the pore structures of these biochars were explored using X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 82 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…The wood-based chars tend to exhibit a higher specific surface area and total C content but a lower CEC and total and available element concentrations than manureand biosolids-based chars [12]. The elemental composition of the water extracts showed the activated charcoal (LG85) to be very poor in available elements, whereas the manurebased BR released K, P and S. Broiler manure is one of the nutrient richest manures and in our previous study [9] the peat bedded broiler manure feedstock was found to contain 24.9, 14.9 and 5.8 g K, P and S per kg dry mass (dm), respectively. The wood-based SA released some K, and the sewage-sludge-based chars mainly released Ca and S but also some N (Table 2, Sect.…”
Section: Char Characteristicsmentioning
confidence: 55%
See 3 more Smart Citations
“…The wood-based chars tend to exhibit a higher specific surface area and total C content but a lower CEC and total and available element concentrations than manureand biosolids-based chars [12]. The elemental composition of the water extracts showed the activated charcoal (LG85) to be very poor in available elements, whereas the manurebased BR released K, P and S. Broiler manure is one of the nutrient richest manures and in our previous study [9] the peat bedded broiler manure feedstock was found to contain 24.9, 14.9 and 5.8 g K, P and S per kg dry mass (dm), respectively. The wood-based SA released some K, and the sewage-sludge-based chars mainly released Ca and S but also some N (Table 2, Sect.…”
Section: Char Characteristicsmentioning
confidence: 55%
“…The targeted process peak temperature was 450-500 °C, and the process was run until the gas formation ceased. Sphagnum peat bedded broiler manure was obtained from Biolan Oy (Eura, Finland), pre-dried at 37 °C and pyrolyzed in a batch-type laboratory-scale pyrolysis equipment [9]. Commercial activated charcoal (SORBOTECH LG85) intended for filtration use was acquired from a local distributor.…”
Section: Tested Charsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the pore properties are affected by choices in the pyrolysis process (e.g., temperature and duration), they are generally more controlled by choice of the feedstock [6,8,11,12]. Particularly wood-based biochars have been found to have desirable properties in terms of porosity, pore size distributions, and surface area [6][7][8], while biochar produced from substances such as manure, sludge, and agricultural residue has often reported to have less suitable pore properties [7,13]. Therefore, from the point of view of pore properties, wood feedstocks can be of particular interest when producing an applicable biochar amendment.…”
Section: Introductionmentioning
confidence: 99%